Surface-Related Features and Virulence Among Acinetobacter baumannii Clinical Isolates Belonging to International Clones I and II - Skerniškytė, Jūratė; Krasauskas, Renatas; Péchoux, Christine; Kulakauskas, Saulius; Armalytė, Julija; Sužiedėlienė, Edita (Frontiers in Microbiology, 2019)
Acinetobacter baumannii currently represents one of the most important nosocomial infection agent due to its multidrug-resistance and a propensity for the epidemic spread. The A. baumannii strains belonging to the international clonal lineages I (IC I) and II (IC II) are associated with the hospital outbreaks and a high virulence. However, the intra and inter lineage-specific features of strains belonging to these most worldwide spread A. baumannii clones are not thoroughly explored. In this study we have investigated a set of cell surface-related features of A. baumannii IC I (n = 20) and IC II (n = 16) lineage strains, representing 30 distinct pulsed-field gel electrophoresis types in the collection of clinical isolates obtained in Lithuanian tertiary care hospitals. We show that A. baumannii IC II strains are non-motile, do not form pellicle and display distinct capsular polysaccharide profile compared with the IC I strains. Moreover, in contrast to the overall highly hydrophobic IC I strains, IC II strains showed a greater variation in cell surface hydrophobicity. Within the IC II lineage, hydrophilic strains demonstrated reduced ability to form biofilm and adhere to the abiotic surfaces, also possessed twofold thicker cell wall and exhibited higher resistance to desiccation. Furthermore, these strains showed increased adherence to the lung epithelial cells and were more virulent in nematode and mouse infection model compared with the hydrophobic IC II strains. According to the polymerase chain reaction-based locus-typing, the reduction in hydrophobicity of IC II strains was not capsule or lipooligosaccharide locus type-dependent. Hence, this study shows that the most widespread A. baumannii clonal lineages I and II markedly differ in the series of cell surface-related phenotypes including the considerable phenotypic diversification of IC II strains at the intra-lineage level. These findings suggest that the genotypically related A. baumannii strains might evolve the features which could provide an advantage at the specific conditions outside or within the host.